Opportunities for Orphan Crops: Expected Economic Benefits From Biotechnology - Zambrano, Patricia; Wood-Sichra, Ulrike; Ruhinduka, Remidius D.; Phillip, Dayo; Nin Pratt, Alejandro; Komen, John; Kikulwe, Enoch Mutebi; Falck Zepeda, José; Dzanku, Fred M.; Chambers, Judith A. (Frontiers in Plant Science, 2022)
An enabling, evidence-based regulatory decision-making framework is critical to support agricultural biotechnology innovation, and to ensure farmers’ access to improved, safe crop varieties. A key element, and often a challenge in the decision-making process, involves the balancing of any identified risks with expected economic benefits from new technologies. The latter is particularly challenging in the case of orphan crops, for which solid economic data are usually scarce. To address this challenge, recent IFPRI studies analyzed the expected economic impacts from planting GM crops in farmers’ fields in sub-Saharan Africa. These studies were based on IFPRI’s modeling tools for ex ante impact analysis and were implemented by local teams in 5 African countries. This article will present key results from this analysis and associated policy recommendations, zooming in on the following orphan crop / trait case studies: a) Insect-resistant cowpea (Nigeria, Ghana) b) Virus-resistant cassava (Uganda, Tanzania) c) Disease-resistant banana (Uganda) The results from case studies listed above project substantial economic benefits to farmers and consumers from the timely adoption of GM crops and show how the benefits might significantly be reduced if there are delays in the approval and adoption process. These findings underscore the importance of having an enabling policy environment and regulatory system — covering, among other elements, biosafety and food/feed safety assessment, and varietal release registration — that is efficient, predictable, and transparent to ensure that the projected economic benefits are delivered and realized in a timely manner.